2020
DOI: 10.1128/aem.01040-20
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Burkholderia xenovorans LB400 BphA through Site-Directed Mutagenesis at Position 283

Abstract: Biphenyl dioxygenase (BPDO), which is a Rieske-type oxygenase (RO) catalyzes the initial dioxygenation of biphenyl and some polychlorinated biphenyls (PCBs). In order to enhance the degradation ability of BPDO in terms of broader substrate range, BphAES283M, BphAEp4-S283M and BphAERR41-S283M variants were created from parent enzymes BphAELB400, BphAEp4 and BphAERR41, respectively by substitution at one residue, Ser283Met. The results of steady-state kinetic parameters show that for biphenyl, the kcat/Km value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Structural analysis suggested that residue 283 located at the entrance of the catalytic cavity, was a key determinant of the catalytic reaction. Our recent reports identified that the single substitution Ser283Met of BphAE LB400 enhanced the catalytic competence toward 2,3 ′ ,4,4 ′ -tetrachlorobiphenyl, 2,2 ′ ,6,6 ′ -tetrachlorobiphenyl and 2,3 ′ ,4,4 ′ ,5-tetrachlorobiphenyl (Li et al, 2020). Although the evolved BphAE S283M , BphAE p4-S283M , BphAE RR41-S283M exhibited an enhanced ability to transform polychlorobiphenyl, their catalytic features toward dibenzofuran had never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural analysis suggested that residue 283 located at the entrance of the catalytic cavity, was a key determinant of the catalytic reaction. Our recent reports identified that the single substitution Ser283Met of BphAE LB400 enhanced the catalytic competence toward 2,3 ′ ,4,4 ′ -tetrachlorobiphenyl, 2,2 ′ ,6,6 ′ -tetrachlorobiphenyl and 2,3 ′ ,4,4 ′ ,5-tetrachlorobiphenyl (Li et al, 2020). Although the evolved BphAE S283M , BphAE p4-S283M , BphAE RR41-S283M exhibited an enhanced ability to transform polychlorobiphenyl, their catalytic features toward dibenzofuran had never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli C41(DE3) (Statagene, La Jolla, CA) was used in this study (Miroux, 1996). In previous work, we evolved BphAE LB400 , BphAE p4 and BphAE RR41 , obtaining BphAE S283M , BphAE p4-S283M and BphAE RR41-S283M (Li et al, 2020).…”
Section: Bacterial Strain and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not focus only on the ecology of aerobic PCB-degrading bacterial strains but also considered the substrate specificity of biphenyl dioxygenases (BphA), which catabolize PCB congeners and are important factors in the trial of this bioaugmentation model. There have been many reports on the substrate specificity of BphA for PCBs, and there have been multiple attempts to genetically modify the enzyme ( 24 28 ). The substrate specificity of BphA for PCB congeners can be roughly divided into two types of biphenyl dioxygenase activities; one is a biphenyl-3,4-dioxygenase activity from a B. xenovorans LB400 strain, and the other is a biphenyl-2,3-dioxygenase activity from another aerobic PCB-degrading bacterial strain, including the LB400 strain.…”
Section: Discussionmentioning
confidence: 99%
“…BphA determines the range of PCB congeners oxidized and plays an essential role in substrate recognition and binding ( 29 ). Genetically modified BphA containing a motif of the BphA gene of the LB400 strain has been investigated in detail ( 26 28 ). We, therefore, constructed a recombinant PCB-degrading bacterium that produced the BphA of the LB400 strain using E. coli as a host strain and confirmed that its substrate specificity was biphenyl-3,4-dioxygenase ( Fig.…”
Section: Discussionmentioning
confidence: 99%